Diagnostic Performance of Gray-Scale US and Elastography in Solid Thyroid Nodules - Moon, Hee Jung; Sung, Ji Min; Kim, Eun-Kyung; Yoon, Jung Hyun; Youk, Ji Hyun; Kwak, Jin Young (Radiology, 2012)
To evaluate the diagnostic performance of gray-scale ultrasonography (US) and elastography in differentiating benign and malignant thyroid nodules. This was an institutional review board-approved retrospective study with waiver of informed consent. A total of 703 solid thyroid nodules in 676 patients (mean age, 49.7 years; range, 18-79 years) were included; there were 556 women (mean age, 49.5 years; range, 20-74 years) and 120 men (mean age, 50.7 years; range, 18-79 years). Nodules with marked hypoechogenicity, poorly defined margins, microcalcifications, and a taller-than-wide shape were classified as suspicious at grayscale US. Findings at elastography were classified according to the Rago criteria and the Asteria criteria. The diagnostic performances of gray-scale US and elastography were compared. For comparison between the diagnostic performances of gray-scale US and the combination of gray-scale US and elastography, three sets of criteria were assigned: criteria set 1, nodules with any suspicious grayscale US feature were assessed as suspicious; criteria set 2, Rago criteria were added as suspicious features to criteria set 1; and criteria set 3, Asteria criteria were added as suspicious features to criteria set 1. The diagnostic performances of gray-scale US, elastography with Rago criteria, and elastography with Asteria criteria, and odds ratios (ORs) with 95% confidence intervals for predicting thyroid malignancy were compared using generalized estimating equation analysis. Of 703 nodules, 217 were malignant and 486 were benign. Sensitivity, negative predictive value (NPV), and OR of gray-scale US for the 703 nodules were 91.7%, 94.7%, and 22.1, respectively, and these values were higher than the 15.7% and 65.4% sensitivity, 71.7% and 79.1% NPV, and 3.7 and 2.6 ORs found for elastography with Rago and Asteria criteria, respectively. Specificity, positive predictive value, and accuracy for criteria set 1 were significantly higher than those for criteria sets 2 and 3 for most of the nodule subgroups that were considered. Elastography alone, as well as the combination of elastography and gray-scale US, showed inferior performance in the differentiation of malignant and benign thyroid nodules compared with gray-scale US features; elastography was not a useful tool in recommending fine-needle aspiration biopsy.